The Person in Personalisation The Story of How Marketing's Most Treasured Possession Became Anything but Personal - Mannheim, David (Brown Dog Books, 2023)
As both practitioners of personalisation and victims of it, it is the person in personalisation that has been lost. The titans of the personalisation industry have commercially defined what personalisation should be for us all without realising what it takes to make a relationship work - a personal touch. This book explores why. And if it can change. - We learn about why we need to dismiss the personalisation perpetual hype, stop reducing it down to a single tactic designed purely to make money. - Instead, we need to rebirth personalisation entirely and engage deeply with what it actually is, what it's supposed to be, and what it means in the future for brands, great and small. Maybe even yours. This book is not like most marketing books - overly inspirational, redundant with revelation, cold and charmless, focusing on dry practicality with arbitrary models that no one can ironically use practically. This is different. Personalisation, spelled with an s, is full of personality, wonder, drama, heroes, and villains, and that all makes for a damn good story. A fairy-tale even. That's how it is written. The Person in Personalisation is an adventure that inspires action from promoting critical thinking with irreverent humour, defeating personalisation dragons (no, really!) encouraging you, the reader, to take things back to basics, not from telling you exactly what to do